Cuantificación de la captura de carbono en las especies forestales y su contribución al ambiente en el Centro de Producción e Investigación Pabloyacu Moyobamba San Martín 2012 - Águila Cobos, Amner Del (2012)
With aimed at quantifying the carbon stored in forest timber species and its contribution to the environment in the forest of the Pabloyacu Research and Production Center, there was calculated the air biomass of the stem of the individuals found in 20,000 m2. There were valued 460 trees contained in four blocks to which the DAP measured up in the species to more than 10 m of diameter; then the species were labelled and put up signs evaluated; the measure of minimal DAP registered was 10,19 cm and the maxim 59,21 cm, and the minimal height of the arboreal species they were 3 m and maximum of 20 m. From the information obtained in the biometric phase (DAP) using the corresponding formulae, there was obtained that, the total quantity of vegetable major biomass was registered in Himatanthussucuuba " Knave caspi " by 7,803 TnC/ha, while in minor quantity in Nectandrareticulada "Moena" with 2.054TnC/ha, being the difference between both species of 5,749 TnC/ha. The estimated carbon in the plant biomass (CBV) of the forest species evaluated stipulate that the greater amount was recorded in Himatanthussucuuba "Bellacocaspi" with 175.57 Tn/ha while in smaller proportion with a 46.21 TNC/ha in Nectandrareticulated"Moena", which implies a difference of 129.38 TNC/ha between both species studied., being species of approximately 10 years.The species that shows relatively high values, after the species mentioned, are "Tullaquiro", Shimbillo" and "Warmiwarmi", values of 138.81, 121.75 and 117.69 TNC/ha respectively. Of 460 evaluated individuals it estimated that the index of wealth the highest sound of Manilkarabidentata's species "Quinilla" with 38,43 and Coumamacrocarpa " Milks caspi " with 38,42 and "Tullaquiro" with 38,41 of index of forest wealth and, with minor index the species of alophyllumbrasiliense "Alfaro", Terminaliaspp. "Almond", Cecropiasciadophytla "Cetico", insipid Ficus "Ojé" with 38.00 of index of wealth. The estimated density in Manilkarabidentata "Quinilla" was 0.0029 with 58 individuals evaluated in an area of 20.000 m2, Coumamacrocarpa "Milk Caspi" of 0.0026 and "Tullaquiro" of 0.0024 , being these forest species with the greatest density registered. In relation to the results reached the following conclusions: through the inventory of the biometric Arboretum of Pabloyacu watershed, there were 460 individuals identified at the level of scientific and common name, which is located in 26 families, being the most frequent, Manilkarabidentata"Quinilla", Coumamacrocarpa"MilkCaspi" and "Tullaquiro". The estimated carbon in the plant biomass of the forest species evaluated stipulate that the greater amount was recorded in imatanthussucuuba "Rogue Caspi" with 175.57 TNC/ha while in smaller proportion with a 46.21 TNC/ha in Nectandra reticulated"Moena"; It is estimated that the evaluated species show a very positive contribution of carbon sequestration to woody biomass level living, because they contribute to the C02reduction into the atmosphere through the flora that stores carbon in its structure through photosynthesis, provides an environmental service in the capture of C02 and for submitting high values in the present investigation.The species that it shows relatively high values of carbon estimated in the vegetable biomass (CBV), later Himatanthussucuuba " Knave caspi ", are "Tullaquiro", Shimbillo "y" Warmiwarmi ", with values of 138.81, 121.75 and 117.69 TnC/ha respectively.